Pemanfaatan Media Sosial dalam Sosialisasi Kesehatan Reproduksi dan Nutrisi untuk Perempuan - Dwi Ajeng Widarini (Jurnal Komunikasi Pembangunan, 2019)
Aisyiyah as one of the Muhammadiyah women's organizations has a means of communication through social media that aims to provide information for progressive women. The Instagram account Aisyiyah currently has 7425 followers with the amount of material posted 561. One of the materials that is the focus of socialization on reproductive health and women's nutrition. As an interactive media tool, Instagram is used to provide knowledge through means of live IG, posting photos, and polling. What is the effectiveness of using Aisyiyah's Instagram account in the dissemination of reproductive health and women's nutrition. The theory used in this study, computer mediated communication. This type of research is qualitative - descriptive with data collection carried out through interviews, observation and literature studies. The results of this study can illustrate the use of social media by Aisyiyah especially in reproductive socialization and nutrition for women.